Rancang Bangun Filter Berbasis Karbon Aktif Tempurung Kelapa, Pasir Silika dan Kerikil Untuk Penjernih Air (Studi Kasus Kampung Tambat Distrik Tanah Miring) - Helena Ines Inez Aries Oriza; Yosefina Mangera; Mega Ayu Yusuf (Musamus AE Featuring Journal, 2023)
The people of Kampung Tambat, Tanah Miring District, Merauke Regency rely on the flow of the Maro River as a water source for processing sago stems into sago starch and also for daily living activities. Even though the water is cloudy, it is still used by the community. This research aims to produce a filter tool based on activated carbon from coconut shell charcoal, silica sand, and gravel to improve the physical quality of Maro River water which is used by the community in processing sago starch. This research uses an experimental method by designing a filter and to determine the performance of the filter, testing equipment and analyzing the physical parameters of water in the laboratory. Research stages: (1) preparation stage, including designing filter equipment, providing tools and materials; (2) the stage of making water purification equipment and installing filter media, namely coconut shell activated carbon, silica sand, gravel, sponge, dacron; (3) filter performance testing stage; (4) test stage for raw water samples and water after filtering in the laboratory which includes parameters, temperature, total dissolve solid (TDS), turbidity, color, odor and pH. The results of laboratory tests on raw water samples show that the physical parameter values of the water meet the Environmental Health Quality Standards for Water Media for Hygiene Purposes (Permenkes No. 2 of 2023), namely temperature, TDS, taste, odor and pH. The test results of Maro River water samples after processing using filters based on activated carbon from coconut shells, silica sand and gravel show that several parameters have experienced a significant decrease even though they are not yet in accordance with the established standards. The test parameters that experienced a decrease were turbidity and color.